2016
DOI: 10.1038/srep39006
|View full text |Cite
|
Sign up to set email alerts
|

Sub-cycle ionization dynamics revealed by trajectory resolved, elliptically-driven high-order harmonic generation

Abstract: The sub-cycle dynamics of electrons driven by strong laser fields is central to the emerging field of attosecond science. We demonstrate how the dynamics can be probed through high-order harmonic generation, where different trajectories leading to the same harmonic order are initiated at different times, thereby probing different field strengths. We find large differences between the trajectories with respect to both their sensitivity to driving field ellipticity and resonant enhancement. To accurately describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 55 publications
5
15
0
Order By: Relevance
“…In a more proper quantum mechanical picture, the extension of the wavefunction of the returning electron results in HHG signal decay as a function of the driver pulse ellipticity [18,19] with the recollision process being less likely for increasing ellipticity. Recent experiments defined the threshold ellipticity (ε th ) as the half-FWHM of this decay [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In a more proper quantum mechanical picture, the extension of the wavefunction of the returning electron results in HHG signal decay as a function of the driver pulse ellipticity [18,19] with the recollision process being less likely for increasing ellipticity. Recent experiments defined the threshold ellipticity (ε th ) as the half-FWHM of this decay [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…[40] This would also affect the recombination process to produce HHG, including the delay time between ionization and recombination. In their study, Larsen et al [41] have shown that the electron excursion time τ of HHG, corresponding with the delay time between ionization and recombination, would be changed upon varying laser ellipticity ε. This fact would in turn affect the position of the dynamic interference minimum, since it is related to the excursion time τ.…”
Section: Resultsmentioning
confidence: 99%
“…The temporal characterisation over a range of 18 − 25eV photon energy is important for studies on the absorption mechanisms in condensed matter such as photoionization of outer valence band electrons, inner electron ionization and Auger transitions. As shown in [38], due to the increased observation time-window provided, the long path high-harmonics are important for HHG spectroscopic studies of molecular dynamics, of relevance to decoherence studies [40]. Our approach based on the combination of scaling invariant loose focusing geometry, two-colour field control, phase matching optimization and far field selection opens perspectives towards the generation of intense XUV pulses with controllable spectral phase distribution.…”
Section: Discussionmentioning
confidence: 99%